The Role of Self-Determination in Linking Humble Leadership to Employee Adaptive Performance - Fikri, Khusnul; Astarina, Ivalaina; Ramadhan, Rian Rahmat; Setianingsih, Rahayu; Alviani, Devi; Marnis, Marnis; Daryanes, Febblina (Jurnal Economia, 2025)
Amid the evolving business environment, traditional performance management models have become less relevant, emphasizing the importance of adaptive performance. Adaptive performance is assumed to be influenced by humble leadership, though its impact may depend on employees' perceptions of the leader's motives. This study, using Self-Determination Theory, aims to examine the role of self-determination as a mediator in the relationship between humble leadership and adaptive performance. Data was collected through a 5-point Likert scale questionnaire from 185 private sector employees in Riau, analyzed using SEM PLS. The results show that humble leadership has a positive impact on adaptive performance, both directly and through self-determination as a mediator.